2002
DOI: 10.1126/science.1070216
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for a Peptidoglycan Recognition Protein (PGRP) in Relish Activation and Antibacterial Immune Responses in Drosophila

Abstract: Components of microbial cell walls are potent activators of innate immune responses in animals. For example, the mammalian TLR4 signaling pathway is activated by bacterial lipopolysaccharide and is required for resistance to infection by Gram-negative bacteria. Other components of microbial surfaces, such as peptidoglycan, are also potent activators of innate immune responses, but less is known about how those components activate host defense. Here we show that a peptidoglycan recognition protein, PGRP-LC, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
406
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 538 publications
(419 citation statements)
references
References 26 publications
7
406
1
1
Order By: Relevance
“…His group demonstrated that a deletion of the Relish gene -which encodes a third Drosophila NF-κB-like protein -produces phenotypes that are similar to those of fruit flies carrying the imd mutation 35,36 . Subsequently, several successful forward genetic screens identified other mutations that, similar to the imd and Relish mutations, render flies highly susceptible to Gram-negative bacterial infections [37][38][39][40][41][42][43] . Surprisingly, none of these mutations affect any detectable functions of the Toll pathway.…”
Section: The Toll and Imd Paradigmmentioning
confidence: 99%
See 1 more Smart Citation
“…His group demonstrated that a deletion of the Relish gene -which encodes a third Drosophila NF-κB-like protein -produces phenotypes that are similar to those of fruit flies carrying the imd mutation 35,36 . Subsequently, several successful forward genetic screens identified other mutations that, similar to the imd and Relish mutations, render flies highly susceptible to Gram-negative bacterial infections [37][38][39][40][41][42][43] . Surprisingly, none of these mutations affect any detectable functions of the Toll pathway.…”
Section: The Toll and Imd Paradigmmentioning
confidence: 99%
“…In contrast to the rapid identification of TLRs and their ligands, the Drosophila molecules involved in microbial recognition remained unknown until recently. At present, we know that some aspects of microbial recognition in flies are mediated by peptidoglycan-recognition proteins (PGRPs) and Gram-negative-bacteria-binding proteins (GNBPs) 43,[56][57][58][59][60] -two protein families identified, initially in other insects, by their capacity to bind microbial components [61][62][63][64] (FIG. 3).…”
Section: Distinct Functions For Toll and Tlrsmentioning
confidence: 99%
“…PGRP-LCa, PGRP-LCx and PGRP-LCy, are generated by alternative splicing; they share common cytoplasmic and transmembrane domains. However, each variant of PGRP-LC has a separate extracellular PGRP domain (x, y or a), and the extracellular PGRP domains are only 39% identical (Choe et al, 2002;Kaneko et al, 2004;Werner et al, 2000Werner et al, , 2003. In mouse, TagL (PGRP-L) has six splicing variants (TagL-α, TagL-β, TagL-γ, TagL-δ, TagL-ε and TagL-μ), which are all identical in the N-terminal portion.…”
Section: Discussionmentioning
confidence: 99%
“…Toll activation initiates signaling that results in the activation of two members of the Rel family transcription factors (similar to mammalian NF-kB), which upon translocation into the nucleus bind kB sites and initiate insect immune response. Isoforms of the insect PGRP-L participate in the Imd pathway of Drosophila, somewhat similar to the mammalian TNF receptor activation of NF-kB [82][83][84] and mediate antimicrobial gene activation upon Grampositive and negative bacteria recognition. [82][83][84][85] None of these cascades was demonstrated for mammalian immune system yet.…”
Section: Innate Immunity Pattern Recognition Molecules In Gene Therapmentioning
confidence: 99%
“…Isoforms of the insect PGRP-L participate in the Imd pathway of Drosophila, somewhat similar to the mammalian TNF receptor activation of NF-kB [82][83][84] and mediate antimicrobial gene activation upon Grampositive and negative bacteria recognition. [82][83][84][85] None of these cascades was demonstrated for mammalian immune system yet. However, our recent findings indicate that both human and mouse Tag7/ PGRP-S are able to induce lymphocyte chemotaxis both in vitro and in vivo, and also induce DC maturation via CD80, CD86 co-stimulatory molecule expression (unpublished results).…”
Section: Innate Immunity Pattern Recognition Molecules In Gene Therapmentioning
confidence: 99%